1989
DOI: 10.1172/jci114262
|View full text |Cite
|
Sign up to set email alerts
|

Familial bone marrow monosomy 7. Evidence that the predisposing locus is not on the long arm of chromosome 7.

Abstract: Loss of expression of a tumor-suppressing gene is an attractive model to explain the cytogenetic and epidemiologic features of cases of myelodysplasia and acute myelogenous leukemia (AML) associated with bone marrow monosomy 7 or partial deletion of the long arm (7q-). We used probes from within the breakpoint region on 7q-chromosomes (7q22-34) that detect restriction fragment length polymorphisms (RFLPs) to investigate three families in which two siblings developed myelodysplasia with monosomy 7. In the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Some data indicate that the inherited predisposing locus in familial MDS or AML with −7/7q− is not located on chromosome 7. 56 This is in accordance with the absence of leukemia cases in a cohort study of 183 persons with constitutional aberrations of chromosome 7. 60 Spontaneous regression of −7 has occasionally been reported in the literature.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Some data indicate that the inherited predisposing locus in familial MDS or AML with −7/7q− is not located on chromosome 7. 56 This is in accordance with the absence of leukemia cases in a cohort study of 183 persons with constitutional aberrations of chromosome 7. 60 Spontaneous regression of −7 has occasionally been reported in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…The development of AML with 7q− in a child with Silver-Russel syndrome is interesting in light of recent data showing uniparental disomy for the entire chromosome 7 in some of these patients. 54 Familial occurrence of MDS with −7/7q− has been reported in a number of cases 10,24,[55][56][57] and has been claimed to account for as many as one-third of the children with −7. 55 We found MDS or AML in relatives of 10 patients.…”
Section: Discussionmentioning
confidence: 99%
“…After osmotic lysis to remove contaminating red blood cells, DNA was extracted from leukocyte pellets by standard methodology as previously described (19,20). DNA samples prepared according to this protocol are from a mixed population of peripheral blood leukocytes (PBLs) that includes lymphocytes, monocytes, neutrophils, and eosinophils.…”
Section: Methodsmentioning
confidence: 99%
“…This was disproved when studies showed different parental origin of the retained chromosome in several sibling pairs with familial monosomy 7. [52][53][54] Although the causative gene has not yet been identified, the pattern of inheritance appears to be autosomal dominant with variable penetrance. Monosomy 7 is not present in the germline in these individuals but instead presents as an acquired abnormality recurring within the family, with the lesion developing at any time in the course of the individual's hematologic disease.…”
Section: Familial Monosomymentioning
confidence: 99%